EFFECTIVE WAYS TO ERADICATE CORRUPTION IN INDONESIA - Dahwir, Ali (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
To eradicate corruption in Indonesia requires extraordinary methods. Such as applying the method that has been used by Denmark and Finland. This research aims to examine and analyze the problem of eradicating corruption in Indonesia. The research method used is qualitative normative juridical, where problems are analyzed using primary legal materials, secondary legal materials and tertiary legal materials. The results of the analysis show that eradicating corruption is a commitment and consistency of each party. The commitment to eradicate corruption can be enforced through good legal substance. Good legal substance can force legal officials to be good. Fighting corruption can be done by setting harsh penalties and a narrow range between the minimum criminal threat and the maximum criminal threat. Confiscation of assets of perpetrators of criminal acts of corruption and instilling anti-corruption values and principles at all levels of education. The threat of severe punishment is carried out top down as a deterrent and bottom up instilling anti-corruption values and principles in society.